Reproductive Equity Support: A Cross-National Comparison of Medically Assisted Reproduction and Abortion Policies - Mio Tamakoshi; Hannah Zagel (Social Inclusion, 2025)
This article offers a new way of classifying and measuring state support for reproductive equity across countries, focusing on medically assisted reproduction (MAR) and abortion. Drawing on the notion of stratified reproduction and comparative welfare state research, we propose a two-dimensional framework to capture how policies can shape different sets of inequalities and how access to reproductive care is provided. The two dimensions that compose our framework are “permissiveness,” the degree to which government policies enable access to reproductive care by legalizing services, defining who qualifies as a patient, and/or imposing restrictive measures on service delivery, and “generosity,” the extent to which government policies subsidize the costs of authorized services for individuals deemed eligible. We applied the permissiveness–generosity framework to quantitative data on MAR and abortion policies from 2020 from the International Reproduction Policy Database across 30 high-income countries. We then investigated the cases of Austria, Germany, and Switzerland, which group together in the overall plotting, more in-depth. The quantitative mapping revealed diverse approaches to reproductive equity, with some countries having both permissive and generous policies, while others focus on one dimension or provide limited support altogether. The case studies show that despite overall trends towards greater reproductive equity in recent decades, state support for individuals' equal access to MAR and abortion remains limited and has taken different pathways in this group of countries. This study contributes to a better understanding of how state policies promote equal access to reproductive care and enable individuals to pursue their desired reproductive pathways, regardless of their characteristics or socioeconomic position.
Keywords: 300; abortion; Austria; Germany; medically assisted reproduction; reproductive equity; stratified reproduction; Switzerland; welfare state